The performance of banking industry in China during 2011-2016: measuring the cost efficiency and analysing the determinants of bank profitability - Li, Jingyu (2017)
The purpose of this dissertation is trying to understand the new economy environment and banking industry conditions in China via analysis the Chinese banks performance during 2011 and 2016 by analysing the cost efficiency and studying the profitability determinants of the banks from different models. The dynamic panel data of 47 listed banks in China from 2011 to 2016 is utilized in models. According to the BC92 model and BC95 model of the Stochastic Frontier Analysis (SFA), the study finds out the efficiency of Chinese banks is good (still can improve) among the listed banks and Chinese banks achieve good scale of economics, but the influence effects exclude the macroeconomic factors which have insignificant effects on bank efficiency. In addition, the commercial banks are slightly less profitable than savings and investment banks. After applying many instrumental variables combine with the Generalized Method of Moments (GMM), the study shows, LODEP, OOITA and NETICH are the main determinants of China’s bank profitability. As the results, Chinese bank industry can improve their profitability by manipulate interest rate, dividend and assets and liabilities structure. Generally, this paper compares bank performance during the last six years and it gives suggestions and recommendations for Chinese banks to improve or reform the banking services and to increase profit of banking businesses.